Survey on Opportunities and Challenges of Urban Forestry in Purbachal Town, Dhaka (Journal of Science and Technology Research, 2026)
A survey was conducted in Purbachal town, Dhaka, to assess the opportunities and challenges of urban forestry in addressing unplanned urbanization issues. A wellstructured interview schedule and systematic random sampling method were used for the data collection during the household survey from June 15, 2023, to July 15, 2023. Main opportunities for urban forestry development in the study area included public willingness to participate in tree plantation activities, government plans, and community forestry expansion; on the other hand, the major constraints included a lack of public space, land fragmentation, and appropriate policy and awareness. The study revealed that urban forestry offered timber production, protection of soil and the environment, reduction of air temperature and pollution, support of biodiversity, and providing educational and research opportunities. In order to enhance urban forestry, the study recommended that the concerned authority organize social groups, build up institutional frameworks, and carry out long-term plantation and management strategies.J. of Sci. and Tech. Res. 6(2): 109-119, 2025